Economic inequality and social entrepreneurship - Pathak, Saurav; Muralidharan, Etayankara (My University, 2018)
This article explores the extent to which income inequality and income mobility—both considered indicators of economic inequality and conditions of formal regulatory institutions (government activism)—facilitate or constrain the emergence of social entrepreneurship. Using 77,983 individual-level responses obtained from the Global Entrepreneurship Monitor (GEM) survey of 26 countries, and supplementing with country-level data obtained from the Global Competitiveness Report of the World Economic Forum, our results from multilevel analyses demonstrate that country-level income inequality increases the likelihood of individual-level engagement in social entrepreneurship, while income mobility decreases this likelihood. Further, income mobility negatively moderates the influence of income inequality on social entrepreneurship, such that the condition of low income mobility and high income inequality is a stronger predictor of social entrepreneurship. We discuss implications and limitations of our study, and we suggest avenues for future research.
Keywords: economic inequality; income inequality; income mobility; multilevel studies; social entrepreneurship